SUATU STUDI TENTANG PARTISIPASI MASYARAKAT DALAM USAHA PELESTARIAN LINGKUNGAN DI DESA KOROLOLAMA KECAMATAN PETASIA KABUPATEN MOROWALI UTARA PROVINSI SULAWESI TENGAH - Arief, Dian Vitaduri; Karwur, Hermon Maurits; Poli, Ellen Eva; Suoth, Grace Feibe Evangelista; Rifani, Irfan (Fakultas Ilmu Sosial dan Hukum, 2025)
He main research problem is how is community participation in environmental preservation efforts in the Korololama Village area District Petasia The aim of the research is to determine community participation in environmental conservation efforts in Korololama Village Qualitative research methods data collection techniques namely observation documentation and interviews Sample data collection was carried out purposively sampling and snowball with research informants namely community leaders village government and residents totaling 9 informants The research results show: 1 Forms of community participation in business conservation carried out in Korololama Village Patasia District Regency Morowali Central Sulawesi Province namely: Taking part in carrying out cleanliness environment take part in social work to organize the environment plant trees for reforestation and provide suggestions regarding conservation and donation efforts monetary donations 2 factors driving community participation in business conservation is carried out because of the role of community leaders there are benefits activities and there is population awareness for environmental preservation and 3 Business government measures carried out by the government to increase community participation in conservation efforts namely: providing guidance motivation and providing funds for environmental conservation activities < em>< p>